I-Witness basura - Philippine Center for Investigative Journalism; GMA News and Public Affairs ([Quezon City] The Philippine Center for Public Affairs, 1999)
Basura examines Metro Manila's worsening garbage problem, and offers solutions, citing communities where garbage is recycled or transformed into compost in their own areas.
"Basura... saw it coming"--Title on container.
Also available in VCD format.
First broadcast on GMA's I-Witness on August 30, 1999.
With funding and support from GMA News and Public Affairs.
Howie Severino, reporter/scriptwriter.
Keywords: Refuse and refuse disposal -- Philippines -- Antipolo City; Sanitary landfills -- Philippines -- Antipolo City; Sanitary landfills -- Leaching. -- Philippines -- Rizal